1997
DOI: 10.1021/bi970594r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preformed Correct Tertiary Interactions on Rapid Two-State Tendamistat Folding:  Evidence for Hairpins as Initiation Sites for β-Sheet Formation

Abstract: The role of preformed correct side chain interactions, such as disulfide bonds, on protein folding kinetics is still not well understood. We investigated the effect of disulfide bond replacements on folding and stability of the small beta-sheet protein tendamistat. Tendamistat folds very fast (tau = 10 ms at pH 7 in water) and without detectable intermediates, which facilitates molecular interpretation of the kinetic data. Tendamistat contains two disulfide bonds, one between cysteines 11 and 27, which connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
62
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 40 publications
10
62
0
Order By: Relevance
“…Our model showed that the disulfide bonds as well as the three hydrogen bonds between the N-terminal loop-0 and strand-6 are of significant importance for the folding of tendamistat (79); without either interaction, the two-state behaviors become unstable or the folding pathway changes significantly. The simulation based on the modified model showed that tendamistat and its two singledisulfide mutants are all two-state folders, consistent with the experimental observations (76,79). By comparing the folding behaviors of the wild-type tendamistat with its two mutants, it was found that the removal of either C11-C27 or C45-C73 disulfide bond leads to a large decrease in the thermodynamical stability and the loss of structure in the unfolded state; and the effect of the former is stronger than that of the latter, as shown in Fig.…”
Section: The Rules Played By Disulfide Bonds In the Folding Process Osupporting
confidence: 82%
See 2 more Smart Citations
“…Our model showed that the disulfide bonds as well as the three hydrogen bonds between the N-terminal loop-0 and strand-6 are of significant importance for the folding of tendamistat (79); without either interaction, the two-state behaviors become unstable or the folding pathway changes significantly. The simulation based on the modified model showed that tendamistat and its two singledisulfide mutants are all two-state folders, consistent with the experimental observations (76,79). By comparing the folding behaviors of the wild-type tendamistat with its two mutants, it was found that the removal of either C11-C27 or C45-C73 disulfide bond leads to a large decrease in the thermodynamical stability and the loss of structure in the unfolded state; and the effect of the former is stronger than that of the latter, as shown in Fig.…”
Section: The Rules Played By Disulfide Bonds In the Folding Process Osupporting
confidence: 82%
“…It is an allb-sheet protein with 74 amino acids and has two disulfide bonds, C11-C27 and C45-C73. There are extensive experimental studies on this protein (72)(73)(74)(75)(76)(77)(78)(79). As a brief summary of these works, tendamistat exhibits a two-state folding behavior that is unique among all the disulfide bonded proteins discovered so far, and this behavior sustains if either disulfide bond is removed (76).…”
Section: The Rules Played By Disulfide Bonds In the Folding Process Omentioning
confidence: 99%
See 1 more Smart Citation
“…Molten globule intermediates usually display a significant exposure of hydrophobic cores to the solvent. Hence, ANS binds strongly to MG and fluoresces intensely (29,30). The dye generally exhibits weak binding affinity to the native and unfolded states of proteins (29).…”
Section: Gdnhcl-induced Unfolding Of Hfgf-1 Is Not a Two-statementioning
confidence: 99%
“…Studies of isolated, water-soluble -hairpins can provide valuable insight into properties of -sheet structure and folding since -hairpins are considered to act as possible nucleation sites for protein folding. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Additionally, their detailed structural interactions can be relevant in developing an understanding of the mechanism for forming various -sheet structures such as found in many (amyloid-like) neurodegenerative diseases in which protein aggregation is an important pathology. [15][16][17][18] During the past decade, there have been many reports discussing de novo designed, water-soluble -hairpin peptide systems, as well documented in several reviews.…”
mentioning
confidence: 99%